1991
DOI: 10.1111/j.1651-2227.1991.tb12010.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding and the Older Infant

Abstract: Prentice, A. (MRC Dunn Nutrition Unit, Cambridge, UK and Keneba, The Gambia). Breast-feeding and the older infant. Acta Paediatr Scand Suppl 374: 78, 1991. The possible benefits and disadvantages to the older infant of breast-feeding being continued after the introduction of solid foods are reviewed. The limited evidence from industrialised countries suggests that prolonged partial breast-feeding has little influence on child health and growth. In contrast, in poor areas of the developing world, the continuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 66 publications
0
18
0
2
Order By: Relevance
“…In industrialised countries there is little evidence for functional eects of breast-feeding during late infancy. A review from 1991 concluded that there was no proof of bene®ts of breast-feeding after the age of 6 months [13]. There are, however, a few more recent studies suggesting that breast-feeding after the age of 6 months protects against lower respiratory tract infections [12] and infections with Haemophilus [16].…”
Section: Introductionmentioning
confidence: 99%
“…In industrialised countries there is little evidence for functional eects of breast-feeding during late infancy. A review from 1991 concluded that there was no proof of bene®ts of breast-feeding after the age of 6 months [13]. There are, however, a few more recent studies suggesting that breast-feeding after the age of 6 months protects against lower respiratory tract infections [12] and infections with Haemophilus [16].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal timing of weaning is still largely discussed in terms of the so-called "weanling's dilemma" (Lutter, 1992): the choice between the known protective effect of exclusive breastfeeding against infectious morbidity, and the insufficiency of breast milk alone to satisfy the infant's energy and micronutrient (e.g., iron) requirements beyond a certain age (McDade and Worthman, 1998;Foote and Marriott, 2003;Wilson et al, 2006;Fewtrell et al, 2007;Kramer and Kakuma, 2009). While modern recommendations suggest that the optimal length of time for exclusive breastfeeding to be at most 6 months (WHO, 2002;Fewtrell et al, 2007;Kramer and Kakuma, 2009), the benefits of continuation of partial breastfeeding during the first 2 years of life has also been demonstrated (Prentice, 1991;Lamberti et al, 2011).…”
mentioning
confidence: 95%
“…Diferenças socioeconômicas sobre o processo de amamentação, abordadas por Prentice (1991), apontaram que, em países industrializados, o prolongamento do aleitamento materno tem influência reduzida sobre as condições de saúde e sobre o processo de crescimento físico das crianças. No entanto, em áreas de carência socioeconômica, especialmente de países em desenvolvimento, o prolongamento da amamentação após o primeiro ano de vida parece exercer um benefício nutricional significativo ao processo de crescimento físico e desenvolvimento das crianças.…”
Section: K C Carrascoza E Colsunclassified